2021
DOI: 10.3389/fonc.2021.651692
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-146a/AKT/β-Catenin Activation Regulates Cancer Stem Cell Phenotype in Oral Squamous Cell Carcinoma by Targeting CD24

Abstract: CD44highCD24low population has been previously reported as cancer stem cells (CSCs) in Oral Squamous Cell Carcinoma (OSCC). Increasing evidence suggests potential involvement of microRNA (miRNA) network in modulation of CSC properties. MiRNAs have thus emerged as crucial players in tumor development and maintenance. However, their role in maintenance of OSCC stem cells remains unclear. Here we report an elevated expression of miR-146a in the CD44highCD24low population within OSCC cells and primary HNSCC tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…For example, Fu LC et.al showed that PD-L1 and β-catenin signaling make up a positive feedback loop to accelerate CSCs expansion and cancer progression by targeting putative stem cell marker LGR5 48 . The activation of miRNA-146a/AKT/β-catenin signaling promotes CSC phenotype in oral squamous cell carcinoma by regulating CD24, a classical maker of CSC 49 . Moreover, β-catenin mediates SOX2 induced-CSC phenotype, metastasis, and chemoresistance of CRC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fu LC et.al showed that PD-L1 and β-catenin signaling make up a positive feedback loop to accelerate CSCs expansion and cancer progression by targeting putative stem cell marker LGR5 48 . The activation of miRNA-146a/AKT/β-catenin signaling promotes CSC phenotype in oral squamous cell carcinoma by regulating CD24, a classical maker of CSC 49 . Moreover, β-catenin mediates SOX2 induced-CSC phenotype, metastasis, and chemoresistance of CRC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, abnormally high expression of miR-146 was seen for the activation of CD24-AKT-β-catenin signaling, which significantly enhanced CSCs proliferation in vitro and tumorigenic ability in vivo [46].…”
Section: Non-melanoma Neoplastic Skin Disorders Squamous Cell Carcino...mentioning
confidence: 99%
“…CD24 is upregulated by HIF1α in human bladder cancer, 97 androgen receptor in urothelial carcinoma, 98 DNA methyltransferase, 99 estrogen receptor 100 and truncated glioma-associated oncogene homolog 1 101 in breast cancer. CD24 expression is negatively regulated by Twist in breast cancer, 102 β-catenin/TCF in colorectal cancer, 103 miR34a 104 and miR-146a 105 in oral squamous cell carcinoma, and histone deacetylase (HDAC) 99 in breast cancer. As a highly glycosylated GPI-anchored protein, the localization of CD24 on the membrane is regulated by the proteins related to both the synthesis of N and O sugars and GPI assembly, such as PIGN, PIGP, and PGAP2.…”
Section: Cd24mentioning
confidence: 99%